A Study of Comparison between the Attitude of Teacher Educators of Self-Financing and Government Colleges of Education: A Comparative Analysis of Attitudes and Professional Values in Teacher Educators (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The expert estimations of teachers of self-financed universities of training is fundamentally higher than the expert estimations of teacher teachers of government schools of instruction. At the point when part proficient esteems were looked at, the mean scores of expert estimations of teacher teachers of self-financed schools of training as for Esthetic Value, Theoretical Value, Religious Value and Social Value were fundamentally higher than the mean score of expert estimations of teacher teachers of government universities of instruction. Be that as it may, the mean scores of expert estimations of teacher teachers of government schools of training regarding Economic Value, Hedonistic Value and Political Value were fundamentally higher than the mean score of expert estimations of educator teachers of self-financed universities of training. It is discovered that the expert estimations of teacher teachers of self-financed universities of training are essentially higher than the expert estimations of educator teachers of government schools of instruction. The teacher teachers of government schools of training must understand this and should introspect and discover the reasons of disintegrating proficient esteems. Teacher teachers must have some sort of responsibility towards their calling. They ought to constantly be associated with their expert development as far as embraced examine, composing research papers, leading workshops and courses, going to gatherings, workshops and classes and showing papers, and so on.